Managing Insurance Fraud - Miller, Gino (2008)
After tax evasion, insurance fraud is considered the highest ranked among white-collar crimes perpetrated today (Coalition Against Insurance Fraud 2001). The complexity of the problem matches its magnitude which arises from a number of sources. Fraud is dynamic: when insurers uncover fraudulent activity and puts up barriers to prevent its reoccurrence, another takes its place. Motivation to commit fraud vary, from opportunistic individuals submitting fraudulent claims as a means of recovering premiums, perhaps encouraged by a shift in public attitudes towards the perception of insurance fraud as a victimless crime and criminal networks that use fraud as a regular source of revenue generation. Moreover, the legal, organisational and commercial constrains under which the insurance industry operates often are negatively impacted depending upon the success of existing fraud prevention, detection and investigation practices.